Current Status of Urological Surgery Clinical Trials in the Middle East and Its Analysis in Comparison to Global - Ozdener, Fatih; Sursal, Alihan; Narter, Fehmi (GALENOS YAYINCILIK, 2019)
Objective: To analyze the rates and types of ongoing urological surgery clinical trials (CTs) in the Middle East (ME) and worldwide. Materials and Methods: The number of urological surgery CTs was identified via the ClinicalTrials.gov database. Studies were further analyzed using different filters present in ClinicalTrials.gov. Results: Vast majority of urological surgery CTs are progressing in North America and Europe with 71.53\%. The ME accounts for only 6.19\%. In the ME, only Turkiye hosts studies of pediatric urological surgery. Additionally, the vast majority of adult studies were also belongs to Turkiye with 64\%. Further, the large portion of conducted CTs in the ME is phase 3 studies and studies with no phase indicated. Similarly, all urological surgery CTs conducted in Turkiye are in later phases or with no phase indicated. Moreover, industry resources are not directed upon these studies in the ME. Few countries use the advantages of industry resources for conducting urological surgery CTs. Conclusion: The ME should be considered as a fertile land for adopting urological surgery CTs due to high population despite low ongoing studies. The lack of industry support in the ME is another problem, which may improve via rendering the ME more attractive for sponsors by adopting new regulatory guidelines for some of the countries.
Keywords: Urological surgery; Clinical trials; Middle East; Urology; Urology industry